2021
DOI: 10.1097/htr.0000000000000708
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Personal and Situational Risk Factors for Traumatic Brain Injury Among Older Adults

Abstract: Objective: To investigate differences between older men and women in Taiwan in personal and situational risk factors for sustaining a traumatic brain injury (TBI) versus soft-tissue injury (STI) due to a fall. Design: Matched case-control study. Participants and Settings: Cases were defined as patients with a primary diagnosis of TBI due to a fall and were identified from those 60 years or older who visited the emergency department (ED) of 3 university-affiliated hospitals in 2015. Matched by the same hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Regarding falls, our results show that women presented more bone injuries and needed more immobilizations after falls. This may be the result of a significant reduction in bone mineral density after menopause, but may also be a consequence of declining motor coordination and having less muscle mass and strength than men 23,35 . Furthermore, gender‐related behaviors could contribute to an increase or decrease in the risk of several diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding falls, our results show that women presented more bone injuries and needed more immobilizations after falls. This may be the result of a significant reduction in bone mineral density after menopause, but may also be a consequence of declining motor coordination and having less muscle mass and strength than men 23,35 . Furthermore, gender‐related behaviors could contribute to an increase or decrease in the risk of several diseases.…”
Section: Discussionmentioning
confidence: 99%
“…This may be the result of a significant reduction in bone mineral density after menopause, but may also be a consequence of declining motor coordination and having less muscle mass and strength than men. 23,35 Furthermore, genderrelated behaviors could contribute to an increase or decrease in the risk of several diseases. In this regard, we found that women more frequently lived alone and had self-reported depression.…”
Section: Discussionmentioning
confidence: 99%
“…The limitation of a study is the absence of the control group to compare the incidence rate between men and women. The outcomes of post TBI depend on the gender [2,[10][11][12][13][14][15][16][17][18]. Different studies suggested that age plays a central role in increasing the risk of TBI [19].…”
Section: Discussionmentioning
confidence: 99%
“…As these scores are the classic assessment methods for STBI patients, they have been widely used in clinical practice. Studies have shown that basic characteristics of patients, such as age and sex, are risk factors for disease severity [ 16 , 17 ]. For example, atrophy of intestinal mucosa can occur in the older people, affecting the absorption and transportation of water and electrolytes [ 18 ].…”
Section: Discussionmentioning
confidence: 99%